2014
DOI: 10.1002/cbf.3032
|View full text |Cite
|
Sign up to set email alerts
|

Lactating and nonlactating rats differ to renal toxicity induced by mercuric chloride: the preventive effect of zinc chloride

Abstract: This study evaluated the effects of HgCl2 on renal parameters in nonlactating and lactating rats and their pups, as well as the preventive role of ZnCl2 . Rats received 27 mg kg(-1) ZnCl2 for five consecutive days and 5 mg kg(-1) HgCl2 for five subsequent days (s.c.). A decrease in δ-aminolevulinic acid dehydratase (δ-ALA-D) activity in the blood and an increase in urine protein content in renal weight as well as in blood and urine Hg levels were observed in lactating and nonlactating rats from Sal-Hg and Zn-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 54 publications
2
12
1
Order By: Relevance
“…Weight reductions during the 30-and 60-day studies could also be attributed to the effect of low dose toxic metals on immature and developing organs of the mice. Immature and developing brain, liver and kidneys are vulnerable to the influence of toxic heavy metals, as they are not developed enough to combat toxicity [38,39]. These findings corroborate work done by Jedhav et al [17] and Antonio Garcia et al [40].…”
Section: Discussionsupporting
confidence: 94%
“…Weight reductions during the 30-and 60-day studies could also be attributed to the effect of low dose toxic metals on immature and developing organs of the mice. Immature and developing brain, liver and kidneys are vulnerable to the influence of toxic heavy metals, as they are not developed enough to combat toxicity [38,39]. These findings corroborate work done by Jedhav et al [17] and Antonio Garcia et al [40].…”
Section: Discussionsupporting
confidence: 94%
“…Several studies have shown that inorganic mercury causes serious kidney damage [6,8,38,44]. In our study, even with the exposure of just one dose of HgCl 2 renal damage was observed by changes in creatinine and urea levels (up 5 and 4 times, respectively) with only some attenuation by pre-treatment with ZnCl 2 combined with NAC (Zn + NAC-Hg) on creatinine levels and by pre-treatment with Zn (Zn-Hg) on urea levels.…”
Section: Discussioncontrasting
confidence: 52%
“…Inorganic mercury also affects liver, blood, intestine, thyroid and testicles [3,4]. In fact, recent studies have demonstrated that animals exposed to mercury chloride (HgCl 2 ) (5 mg/kg) present renal [5][6][7][8], hepatic [9][10][11][12], testicular [13], behavioral [14,15] and cardiovascular [16] alterations.…”
Section: Introductionmentioning
confidence: 99%
“…This similarity may be due to the biotransformation of a fraction of methylmercury to Hg 2+ resulting in accumulation of Hg 2+ in addition to methylmercury. Since the kidney is the primary site of accumulation of Hg 2+ in dams (Bridges and Zalups, 2010; Favero et al, 2014a; Zalups, 2000), it is not surprising that it is also the primary site of accumulation in the fetus. Furthermore, these findings indicate that accumulation of Hg 2+ in fetal organs is dependent upon the dose of Hg 2+ received by the dam.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in as little as three hours after intravenous exposure to Hg 2+ (as HgCl 2 ), approximately 55% of the administrated dose can be detected in the kidneys (Zalups, 1993). In animals exposed to nephrotoxic doses of HgCl 2, pathological changes such as cellular necrosis, tubular dilatation and atrophy, proteinaceous casts, inflammation, and interstitial collagen deposition have been identified in and around proximal tubules (Bridges et al, 2014; Favero et al, 2014b). Increases in blood urea nitrogen (BUN) and plasma creatinine levels have also been reported, which suggests that glomerular filtration rate (e.g., renal function) is reduced following exposure to highly nephrotoxic doses of HgCl 2 (Bridges et al, 2014; Zalups et al, 2014).…”
Section: Introductionmentioning
confidence: 99%